The Environmental Gaze: Reading Sartre through Guido van Helten's No Exit Murals - Balay, Joe (Lexington Books, 2023)
Following Guido van Helten’s provocative reimagination of Jean-Paul Sartre’s No Exit, The Environmental Gaze: Reading Sartre through Guido van Helten’s No Exit Murals offers an environmental reading of Sartre’s theory of the gaze (le regard). Joe Balay argues that while Sartre is commonly associated with the longstanding humancentric bias in Western thinking, a closer reading shows that his phenomenology of vision involves a powerful environmental story. On the one hand, this is demonstrated by the way that the social worldview contributes to a progressive alienation from our bodies and the natural world around us, culminating in the loss of the Earth in Sartre’s play. On the other, Balay argues that the artwork serves as a pivotal interruption of this alienation, inviting us to see the world anew through an inter-human-natural mode of perception that we might call the environmental gaze. In this way, this book makes a strong case for the significance of Sartre’s work and for the place of art in facing our environmental reality today.